T2 : the future war - Stirling, S. M. (New York : EOS, 2009)
Sarah and John Connor are hiding out in Alaska, hoping to escape from the Cyberdyne Corporation, but when they learn the corporation is in the process of creating an artificial intelligence network designed to destroy the world, they emerge from their remote home to try and save humanity.
"Based on the world created in the motion picture written by James Cameron and William Wisher."
Adult.
Adult
Keywords: Artificial intelligence -- Fiction; Good and evil -- Fiction; Artificial intelligence -- Fiction; Good and evil -- Fiction; Science fiction; War stories; Science fiction; War stories